3-레벨 하이브리드 ANPC 인버터의 커패시터 리플 전류 및 공통 모드 전압 저감을 위한 공간 벡터 변조 기법 - 안상원 (The Graduate School, Ajou University, 2021)
This thesis proposes a space vector modulation to reduce capacitor ripple current and common-mode voltage of three-level hybrid ANPC (Active Neutral-Point-Clamped) inverter. Recently, researches on hybrid type inverters composed by IGBT and MOSFET have been actively conducted. Hybrid ANPC inverter operates at low frequency for IGBT and high frequency for MOSFET, thereby minimizing losses in the inverter. Voltage source inverters such as hybrid ANPC utilize a capacitor as a DC link. Capacitors are one of the most fragile components in the power conversion system. When a large ripple current flows through the capacitor, the wear-out of the capacitor is accelerated. In addition, CMV (Common-Mode Voltage) generated from the PWM inverter causes harmful effects such as leakage current, bearing current, and EMI (Electromagnetic Interference), which lowers the reliability of the system. SVM (Space Vector Modulation), which is widely used because of its outstanding THD (Total Harmonic Distortion) characteristics and high MI (Modulation Index) level, does not consider the capacitor ripple current and CMV. In this thesis, modified space vector modulation for reducing capacitor ripple current and CMV is proposed to improve the reliability of hybrid ANPC inverter. The validity of the proposed SVM is verified by the simulation and experimental results.
학위논문(석사)--아주대학교 일반대학원 :전자공학과,2021. 2
Keywords: 공간 벡터 변조 기법; 신뢰성; 커패시터